2019
DOI: 10.1186/s13229-019-0293-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of ubiquitin ligase E3A in polarized contact guidance and rescue strategies in UBE3A-deficient hippocampal neurons

Abstract: BackgroundAlthough neuronal extracellular sensing is emerging as crucial for brain wiring and therefore plasticity, little is known about these processes in neurodevelopmental disorders. Ubiquitin protein ligase E3A (UBE3A) plays a key role in neurodevelopment. Lack of UBE3A leads to Angelman syndrome (AS), while its increase is among the most prevalent genetic causes of autism (e.g., Dup15q syndrome). By using microstructured substrates that can induce specific directional stimuli in cells, we previously foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 71 publications
3
19
0
Order By: Relevance
“…Recently, another study on axonal dynamics was conducted. Axon and dendrite contact guidance of AS hippocampal neurons was assessed on micrograting substrates that can provide a directional stimulus in vitro . Axonal guidance deficit and increased axonal branching with frequent secondary axonal segments were found to be related to the UBE3A loss.…”
Section: Molecular Pathogenesis: the Contribution Of The Hippocampusmentioning
confidence: 99%
“…Recently, another study on axonal dynamics was conducted. Axon and dendrite contact guidance of AS hippocampal neurons was assessed on micrograting substrates that can provide a directional stimulus in vitro . Axonal guidance deficit and increased axonal branching with frequent secondary axonal segments were found to be related to the UBE3A loss.…”
Section: Molecular Pathogenesis: the Contribution Of The Hippocampusmentioning
confidence: 99%
“…Only neurons fully visible and with soma cleanly abutting neighbouring cells were traced and analysed. Neurites were semi-automatically segmented by NeuronJ, according to their branching, as in 69,70 . Briefly, neurite segments were divided in categories: 1° order for neurites directly emerging from the cell soma (from soma to the tip); 2° order for neurites emerging from 1° order neurites.…”
Section: Focal Adhesion Experiments and Live Cell Total Internal Reflmentioning
confidence: 99%
“…Briefly, neurite segments were divided in categories: 1° order for neurites directly emerging from the cell soma (from soma to the tip); 2° order for neurites emerging from 1° order neurites. We focused our analysis on 1° order neurites, being them the vast majority of total neuritic segments at early stages 55,69 . Neurite analysis was then performed such as for PC12 cells, as reported above.…”
Section: Focal Adhesion Experiments and Live Cell Total Internal Reflmentioning
confidence: 99%
“…Notably, some novel cell morphologies which in part dictates the cell such as contact guidance (Nguyen et al, 2016;Ray et al, 2017) and cell bridges (Goldner et al, 2006;Zhang et al, 2015b), have been observed on the patterned substrates at micro and nano scale. While contact guidance has been extensively investigated in regeneration medicine and tissue engineering (Kamyar et al, 2018;Tonazzini et al, 2019), studies on cell bridges observed on chemical pattern substrates and some nano/micro topographical substrates remain scarce.…”
Section: Introductionmentioning
confidence: 99%
“…With the recent advancement of tissue engineering, cell biology, and biomaterials science, various substrates or scaffolds with more defined topographic (Zhao et al, 2018) and chemical (Na et al, 2017) pattern are prepared to mimic the natural cell niche in tissue in order to guide the cells behavior. Contact guidance (Zhang et al, 2015a;Tonazzini et al, 2019), cell adhesion (Vasiliki and Triantafyllos, 2018), differentiation (Yao et al, 2016;Zhang et al, 2019) and gene expression (Qiongfang et al, 2018) have been paid much attention and investigated extensively; however, cell bridges, a phenomenon as consistent as contact guidance remain to be completely elucidated. As an essential behavior of cells, cell bridges may play crucial role in organization of cells, migration and development.…”
Section: Introductionmentioning
confidence: 99%